Organizing The Teaching Process Of The Physics Course Based On Interdisciplinary Connections (Journal of Pedagogical Inventions and Practices, 2025)
This article focuses on enhancing the effectiveness of the teaching process on the basis of interdisciplinary connections, drawing on the work carried out at leading centers specializing in pedagogical research. It examines the definitions of interdisciplinary connections provided in the scientific and methodological works of prominent scholars. The concepts of interdisciplinary education and various didactic and methodological approaches are analyzed, and their application in teaching physics is explored. Based on the research findings, a definition of interdisciplinary connections and a schematic representation of how to organize the teaching process using these connections are provided.